EXPERIENCE OF ORGANIZING TRAINING OF PROFESSIONALS FOR HIGH-TECH INDUSTRIES - Oleg N. Gorshkov; Kirill A. Markov; Vladimir N. Chuvil'deev (Moscow Polytechnic University, 2016)
The article describes some approaches to the organization of training of professionals for high-tech industries at the UNN Faculty of Physics using the resources of the Physical-Technical Research Institute of UNN. The paper presents a number of successful results of this activity. It is shown that the combination of fundamental training carried out at the classical Faculty of Physics and practical training at the Research Institute focused on the application of research results in the industry ensures a new level of quality for the competences of the University graduates.